Chitosan-Based Mucoadhesive Vaginal Tablets for Controlled Release of the Anti-HIV Drug Tenofovir - Raúl Cazorla-Luna; Fernando Notario-Pérez; Araceli Martín-Illana; Roberto Ruiz-Caro; Aitana Tamayo; Juan Rubio; María Dolores Veiga (MDPI AG, 2019)
Vaginal microbicides have the potential to give women at high risk of contracting HIV the option of self-protection by preventing the sexual transmission of the virus. In this paper, mucoadhesive vaginal tablets based on chitosan, alone and in combination with pectin and locust bean gum, were developed for the sustained release of tenofovir (an antiretroviral drug). The formulations were placed in simulant vaginal fluid (SVF) to swell, and Hg porosity and SEM microscopy were used for the microstructural characterization of the swelling witnesses. The results show that the association of pectin and chitosan generated polyelectrolyte complexes and produced a robust system able to maintain its structure during the swelling process, when small pores are formed. Drug release and bovine vaginal mucoadhesion studies were performed in SVF showing that tenofovir-controlled dissolution profiles and adhesion to the mucosa were conditioned by the swelling processes of the polymer/s in each formulation. Tablets based on chitosan/pectin have the most homogeneous tenofovir dissolution profiles and last up to 96 h, remaining attached to the vaginal mucosa for the same period. These formulations can therefore be considered a good option for the self-protection of women from the sexual transmission of HIV.